Customary Sanctions in the Perspective of Fiqh: Local Wisdom and Social Harmony in North Aceh - Muslem Muslem; Syahrizal Abbas; Mursyid Djawas; Zahrul Mubarrak; Supriadi Supriadi (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2023)
The customary law practiced within a community reflects a system of values and norms passed down through generations. One such regulation is the prohibition of activities such as farming, gardening, and fishing on certain days particularly on Fridays as a form of respect for the obligation of performing Friday prayers. This study aims to examine the philosophical foundations, alignment with Islamic jurisprudence (fiqh), and the effectiveness of the implementation of customary sanctions in North Aceh Regency. The study reveals the complex interaction between traditional customs and the principles of Islamic law in the formulation of these sanctions. The research employs an empirical juridical method, with a normative approach focusing on the analysis of customary legal norms prevailing in the local community. The subjects were selected through purposive sampling, involving interviews with religious leaders (ulema), traditional leaders, mukim, customary institutions, and the local community of North Aceh. The findings indicate that the philosophical rationale behind the formulation of customary sanctions in North Aceh aligns with fiqh principles, aiming to preserve traditional values and local culture as integral components of community life. These sanctions are based on principles of justice, solidarity, social responsibility, and social order, with the goal of restoring communal harmony disrupted by violations of local norms. The formulation process involves collaboration between Islamic scholars and traditional leaders through the study of Islamic texts, the Qur’an, and Hadith, alongside discussions about local customary practices. The implementation of customary sanctions is considered effective, as it continues to be respected and upheld by the community. However, challenges persist in the form of declining knowledge and concern among younger generations regarding customary law. This study recommends the preservation of customary values rooted in Islamic principles through educational and participatory approaches across generations.